Muscle pain syndromes and fibromyalgia: the role of muscle biopsy. Issue 3 (September 2018) - Ruggiero, Lucia; Manganelli, Fiore; Santoro, Lucio
Abstract : Purpose of review: Muscle pain syndromes are extremely frequent cause of chronic disability, and a muscle biopsy is often performed to achieve a diagnosis when myalgia has a myopatic origin. Instead, the role of muscle biopsy in fibromyalgia is controversial. This review examines the reported studies with the objective to evaluate if some changes exist in the muscle, if these changes produce pain and if muscle biopsy is helpful in diagnostic flowchart of fibromyalgia. Recent findings: Recent studies focused on functional side (muscle metabolism and the altered expression of proteins) hypothesize the role of peripheral factors in the maintenance of chronic pain. The results of some studies show the increased concentration of the end products of anaerobic glycolysis and a damage in oxidative metabolism caused by localized hypoxia. In addition, it is present as an insufficient capacity of promoting muscle recovery with inflammation and in metabolic pathway alterations. Unfortunately, these changes are nonspecific and the importance of peripheral factors remains under debate. Summary: Morphological and metabolic changes exist in muscle of patients with fibromyalgia but they are not specific and are not sufficient for a definite diagnosis. Nevertheless, the results obtained so far indicate a role of peripheral factors for maintaining the intensity of pain. Therefore, it is desirable to have a better understanding of peripheral muscle alteration that could open up for new therapeutic strategies.